EARLY DETECTION OF BIOMECHANICAL-BIOHEMICAL IMBALANCE OF FLAT FOOT IN CHILDREN AND IMPLEMENTATION OF PATHOGENETIC ORIENTED THERAPEUTIC TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Children's shoes are culturally recognizable, immobilized, and screening standards are not standardized, as well as the inertia of the so-called "mechanic of the knee = sufficien" in orthopedics, which has led to the restoration of the condition in pediatric surgery. Is it possible to weaken the shock-absorbing function of the dome, to reduce the center of the medial tissue of the body, to reduce the kinematics of the torso to the "yoke tash" mode, and to check the supination of the spinal cord. Postural postural The Communist Party of China (CCP) has been criticized for its lack of transparency in the regulation of collagen metabolism by the Communist Party of China.